The God of Small Things - Roy A. Arundhati (London, Flamingo, 1997)
Set against a background of political turbulence in Kerala, this novel tells the story of twins Esthappen and Rahel. Amongst the vats of banana jam and heaps of peppercorns in their grandmother`s factory they try to craft a childhood for themselves amidst what constitutes their family.